Optimization of thermo-mechanical and antibacterial properties of epoxy/polyethylene glycol/MWCNTs nano-composites using response surface methodology and investigation thermal cycling fatigue - Ashrafi, M.; Ghasemi, A. R.; Hamadanian, M.
This work aimed to develop mechanical/thermal properties of polymer-based nanocomposite in aerospace applications. Hence, herein nanocomposites were prepared through the direct blending of epoxy (EP)with Polyethylene glycol (PEG)and multiwalled carbon nanotubes (MWCNTs)as filler. Weight fraction of fillers was optimized by central composite design (CCD)to get maximum tensile strength and elongation. Interestingly, cross-section scanning electron microscopy (cross-section SEM)and thermal gravimetric analysis (TGA)observations revealed that MWCNTs were well dispersed on polymer matrix and thermal stability of EP was strengthened. The optimized EP/PEG/MWCNTs nanocomposites were tested under 150 thermal cycles and results were shown elongation 24.83 percent and tensile strength 17.96 percent were decreased after 150 cycles. Also, cross-section SEM images clearly showed that the fractures have increased slightly. In addition, MWCNTs-Ag nanostructures were synthesized and EP/PEG/MWCNTs-Ag nanocomposites were prepared for investigation antibacterial activity. Energy dispersive spectroscopy (EDS)mapping images of MWCNTs-Ag were confirmed the homogeneous and efficient anchoring of silver on the MWCNTs. Results indicate that, Ag nanoparticles can be enhanced the antibacterial activity of EP/PEG/MWCNTs.
Keywords: MECHANICAL/THERMAL PROPERTIES; POLYMERIC NANOCOMPOSITE; EP/PEG/MWCNTS; THERMAL CYCLE LOADING; ANTIBACTERIAL PROPERTY